ANALISIS HUBUNGAN PROSEDUR, ALAT DAN LINGKUNGAN KERJA TERHADAP KESELAMATAN KERJA PROYEK KONSTRUKSI (STUDI KASUS PEMBUATAN TANGKI DI PT KUTAI REFINERY NUSANTARA) - Ananta, Erwin; Maslina, Maslina; Pakonglean, Abigail Marlina (IDENTIFIKASI, 2021)
Development is basically a process of change that leads to better results, among others, through the process of economic growth. The process of economic development is carried out through economic activities in various sectors, including the industrial sector which requires business management and among which requires the support of Occupational Safety and Health (K3). Construction work is work that involves engineering consultants as front-end engineering and design planners as well as detailed engineering design contractors as executors as well as supervisory consultants. Construction work is a solid job of activities with a high enough level of risk such as heavy lifting work, working at height and limited space work the effects of the work in the event of an accident include damage to the equipment used, damage to the environment around the project and loss of workers' lives and the latter effect is called fatality as a whole these effects will affect the schedule of the project. project elesaian as well as swelling construction costs. Based on data from the Social Security Organizing Agency (BPJS) Employment 2015, the number of work accidents reached 105,182 cases of the total, 38% of the total was accidents of workers falling from a height. Falling from a height is a very large risk that can occur in workers who carry out construction activities at high elevations. Usually, this incident will result in a fatal accident. Keywords: Tools, Environment, Procedures